Strong optical, electrical, and Raman in-plane anisotropy in corrugated two-dimensional perovskite - Lekina, Yulia (2022)
Combining the unique properties of hybrid halide perovskites and in-plane anisotropic potential of two-dimensional materials, corrugated layered perovskites are excellent candidates for novel optoelectronic devices. Here, we report strong in-plane anisotropy in a two-dimensional hybrid halide perovskite with corrugated inorganic sheets. We assigned the angle-dependent Raman spectra to particular orientations of the crystals where the method applied is suitable for fast determination of the in-plane crystallographic axes. We demonstrated strong in-plane anisotropy of the optoelectronic properties: electrical measurements showed that changes of photoconductivity and angle-resolved reflectance spectroscopy exhibited variation of the band structure. Employing first-principles calculations, we confirmed the observed anisotropy of the dielectric response. Photoluminescence spectroscopy revealed an anomalous energy shift of μ20 meV dependent on the relative orientation of the crystals and polarization of the excitation light. Using temperature-dependent analysis of the photoluminescence spectra, we obtained the anisotropic exciton-phonon coupling strength as well as the angle-dependent average phonon energy involved, which contributes to the shift of the photoluminescence peak maximum. This discovery of the in-plane anisotropic behavior in layered 2D perovskites could be expected to spur new functionalities in optical and optoelectronic device applications.